Green Accounting dan Environmental Innovation: Sustainable Growth Strategies Pada Sektor Consumer Non-Cyclicals - Bela Feronika; Shinta Permata Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The growing concern for sustainability issues in the business world has encouraged companies to pay more attention to environmental, social, and economic aspects. This study aims to analyze the influence of Sustainability Reporting, Green Accounting, Environmental Performance, and Green Innovation on Sustainable Growth Rate. The research focuses on consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. A total of 96 companies are selected as samples using a purposive sampling technique. A quantitative approach is applied, using secondary data collected from the official website of the Indonesia Stock Exchange. Data analysis is performed using multiple linear regression. The results of this study indicate that Sustainability Reporting has an effect on the Sustainable Growth Rate, showing that the quality of sustainability disclosure reflectsthe company’s commitment to maintaining a balance between social responsibility and long-term operational performance. Green Ac counting has no effect on the Sustainable Growth Rate, showing that this practice has not been fully and consistently implemented in most companies. Environmental Performance affects the Sustainable Growth Rate, emphasizing the importance of environmental achievements in maintaining corporate stability and reputation. Green Innovation also has an effect on the Sustainable Growth Rate, showing that environmentally based innovation plays a vital role in maintaining competitiveness and supporting long-term corporate sustainability. This study provides an overview of sustainability practices enhance the sustainable growth of companies.